Accessibility Analysis for the Elderly in an Urban Area from Turkey - Aslı BOZDAĞ; Münevver Gizem GÜMÜŞ; Kutalmış GÜMÜŞ; Savaş DURDURAN (Transylvanian Review of Administrative Sciences, 2017)
An increasing population as a result of urbanization brings with it the need for an urban regeneration process. This process is particularly crucial to ensure that elderly people with limited mobility are able to meet their own needs as well as participate in the social dynamics of the city. Depending on their mobility, the accessibility capability of elderly people is one of the key dynamics of the urban planning process, and accessibility is particularly important for elderly people with regard to covering their needs. The aim of this study was to examine the capability of elderly people, whose needs are typically neglected in the urban planning process, in accessing spatial services in Niğde, a city located in the Central Anatolian region of Turkey. The literature was reviewed to identify areas frequented by elderly users, as well as the level of accessibility of such areas. A survey was then conducted to determine the level of importance attached by the elderly to the accessibility of these spatial services. Based on the fi ndings of the survey, a spatial analysis was conducted for the city using the Geographical Information System (GIS), and accessibility impact areas were identifi ed. The inadequacies of urban areas in Niğde were identifi ed, and various recommendations were proposed in order to resolve them.